Diaphragmatic excursion: Quantitative measure to assess adequacy of expiratory phase CT chest images. Issue 136 (March 2021) - Azour, Lea; Mendelson, David S.; Rogers, Linda; Salvatore, Mary M.
Highlights: Diaphragmatic excursion (DE) correlates with change in lung volume on expiratory imaging. Patients may not demonstrate a change in tracheal morphology between inspiratory and expiratory phase imaging. DE is an easily derived metric that can be used to determine if there has been a satisfactory end-expiratory effort. Abstract: Objective: To evaluate diaphragmatic excursion as a quantitative metric for change in lung volume between inspiratory and expiratory chest computed tomography (CT) images. Methods: A 12-month retrospective review identified 226 chest CT exams with inspiratory and expiratory phase imaging, 63 in individuals referred with diagnosis of asthma by ICD9/10 code. Exams acquired in the supine position at 1.25 mm slice thickness in each phase were included (n = 30, mean age = 62, M = 15, F = 15). Diaphragmatic excursion was calculated as the difference between axial slices through the lungs on inspiration and expiration, using the lung apex as the cranial bound, and the hemidiaphragm caudally. Inspiratory and expiratory lung and tracheal volumes were calculated through volumetric segmentation. Tracheal morphology was assessed at 1 cm above the level of the aortic arch, and 1 cm above the carina. Results: Inspiratory and expiratory lung volumes were higher in men (mean I = 5 + 1.6 L, E = 3.1 + 1.2 L) than women (mean I = 3.6 + 0.8 L, E = 2.4 + 0.7 L), p = .005 and p = .047, respectively. Average inspiratory and expiratory tracheal volumes were higher in men (I = 61 + 17 mL, E = 43 + 14) than women (I = 44 + 14, E = 30 + 8), p = .006 and p = .005. Average change in lung and tracheal volume between inspiratory and expiratory scans did not significantly differ between men and women. Average diaphragmatic excursion was 2.5 cm between inspiratory and expiratory scans (2.7 cm in men, 2.3 cm in women; p = .5). There was a strong positive correlation between diaphragmatic excursion and change in lung (r = .84) and tracheal volume (r = .79). A moderate correlation was also found between change in tracheal volume and change in lung volume (r = 0.67). Change in tracheal morphology between inspiratory and expiratory imaging was associated with change in tracheal volume at both 1 cm above the aortic arch (p = .04) and 1 cm above the carina (p = .008); there was no association with diaphragmatic excursion or lung volume. Conclusions: Diaphragmatic excursion is a quantitative measure of expiratory effort as validated by both lung and tracheal volumes in asthma patients, and may be more accurate than qualitative assessment based on tracheal morphology.